Synthesis, in Vitro Studies of Monocarbonyl Curcumin Analog Compounds Against Breast Cancer Cells and Normal Vero Cells, and In Silico Studies on Protein Variation - Astuti, Endang; Rahmawati, Widya; Sulistya, Rahmawati; Chabib, Ircham Nur; Wahyuningsih, Tutik Dwi; Raharjo, Tri Joko; Mardjan, Muhammad Idham Darussalam (Molekul, 2026)
ABSTRACT. The research aims to synthesize monocarbonyl analogs of curcumin (MAC) and evaluate their anticancer activity. The synthesis was carried out by sonication method through Claisen-Schmidt condensation reaction using base catalysts, namely potassium hydroxide and sodium hydroxide. Characterization of the compounds was carried out using TLC Scanner, ATR-IR, 1H-NMR, and 13C-NMR. Monocarbonyl analog of curcumin compounds A, B, and C have been successfully synthesized with purity of 91.13; 95.82; and 87.57%, respectively. The resulting compounds are yellow solids and have good yields. The monocarbonyl analog of curcumin compounds were then tested for cytotoxicity against breast cancer cells (T47D, MCF-7, and 4T1) and normal cells (Vero). Pharmacokinetic prediction and toxicity (ADMET) was performed using an online site (pkCSM). Monocarbonyl analogs of curcumin compounds were predicted to have a better pharmacokinetic profile compared to curcumin. Molecular docking was carried out using Autodock Vina to determine the interaction of curcumin and monocarbonyl curcumin analog compounds with EGFR, Bcl-2, and p53 mutants. Based on molecular docking, the proposed monocarbonyl analogs of curcumin generally exhibit lower binding affinities that curcumin and form specific interactions with amino acid residues inf target proteins. Keywords: Claisen-Schmidt condensation, molecular docking, monocarbonyl analog of curcumin.